2019
DOI: 10.1021/acsami.8b19148
|View full text |Cite
|
Sign up to set email alerts
|

Nesting Co3Mo Binary Alloy Nanoparticles onto Molybdenum Oxide Nanosheet Arrays for Superior Hydrogen Evolution Reaction

Abstract: Transition-metal alloys have attracted a great deal of attention as an alternative to Pt-based catalysts for hydrogen evolution reaction (HER) in alkaline. Herein, a facile and convenient strategy to fabricate Co3Mo binary alloy nanoparticles nesting onto molybdenum oxide nanosheet arrays on nickel foam is developed. By modulating the annealing time and temperature, the Co3Mo alloy catalyst displays a superior HER performance. Owing to substantial active sites of nanoparticles on nanosheets as well as the intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 60 publications
2
49
3
Order By: Relevance
“…The alloys show overpotentials of 120 ± 5 mV (Co 3 Mo) and 160 ± 5 mV (Co 7 Mo 6 ) at 10 mA cm −2 . In comparison with recently reported Co 3 Mo on nickel foam, the observed overpotential seems high [20]. Chen et al reported the overpotentials of 78 mV (C DL = 15.8 mF cm −2 ) and 75 mV (C DL = 17.5 mF cm −2 ).…”
Section: Resultscontrasting
confidence: 51%
See 4 more Smart Citations
“…The alloys show overpotentials of 120 ± 5 mV (Co 3 Mo) and 160 ± 5 mV (Co 7 Mo 6 ) at 10 mA cm −2 . In comparison with recently reported Co 3 Mo on nickel foam, the observed overpotential seems high [20]. Chen et al reported the overpotentials of 78 mV (C DL = 15.8 mF cm −2 ) and 75 mV (C DL = 17.5 mF cm −2 ).…”
Section: Resultscontrasting
confidence: 51%
“…In other words, based on this approximation Co7Mo6 can deliver 2.7 times higher current densities, as demonstrated in Figures S10 and S11, which also leads to an improved overpotential of 123 mV at 10 mA cm -2 . This is an interesting result, especially given that recent DFT calculations on Co3Mo have shown that Mo-atoms are the catalytic sites in Co3Mo [20]. One can assume that increasing the amount of Mo would lead to improved catalytic performance.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations